The Influence Of Online Customer Reviews, Online Customer Ratings and Price Consciousness on Purchasing Decisions in Shopee E-Commerce on Gen Z Sub-District Binawidya Pekanbaru City - Nuha, Ulin; Rachmad, Ferizal (Basecamp Economics PubMed, 2024)
This research was conducted in gen z, Binawidya District, Pekanbaru City. The aim of this research is to analyze the influence of online customer reviews, online customer ratings and price consciousness on purchasing decisions in Shopee e-commerce in Gen Z, Binawidya District, Pekanbaru City. The data collection technique uses a questionnaire. The type used in this research is a quantitative type regarding the influence between variables. Research data was analyzed using SPSS version 24. The sample in this study was Gen Z, Binawidya District, Pekanbaru City, totaling 96 people using the purposive sampling method. Based on the results of this research, it shows that Online Customer Reviews, Online Customer Ratings and Price Consciousness influence purchasing decisions both partially and simultaneously. The results of the Coefficient of Determination (R2) show that the R square value is 0.770 or 70%, indicating that the variables Online Customer Review, Online Customer Rating and Price Consciousness as a whole have an influence of 70% on purchasing decisions. Meanwhile, the remaining 30% is influenced by line variables which were not examined in this research.